Spatial Analysis of Educational Services Using GIS in Nasiriyah City (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Geographic Information Systems (GIS) are becoming useful and important tools for making strategic decisions whenever reliable data on spatial distribution are found, finding suitable sites for educational areas is important, as schools located in a strategic and safe area play an important role in building up students' skills in the future. The objective of the present work is therefore to firstly evaluate the educational services in Nasiriyah city in its regional context and to suggest educational services in the city of Nasiriyah in its regional context and to suggest long-term options for their development.Secondly, it aims to outline the measures necessary to ensure the orderly development of the expansion of educational needs within urban limits, and to provide for the Spatial analysis for education services in the city. The Geographic Information System (GIS) has been implemented as a multi-criteria spatial analysis tool. Results with some of the implemented standards based on (GIS) using ArcGIS 10.3 Network Analyst (Service Area) tool and Excel Office as statistical software.